Tetraethynylmethane: A Quest for the “Dutch Diamond” - Beil, Sebastian B. (Synlett, 2025)
Tetraethynylmethane is an elusive building block that has motivated generations of organic chemists to provide an efficient synthesis. Despite being thermally unstable, several reports have culminated in its effective synthesis, and initial applications as porous material were described. However, the uniqueness of this molecule has not reached its full potential, both from a synthetic and applied point of view.
Keywords: Alkyne; Synthesis; Symmetric; Porous materials; Tetraethynylmethane